Prognostic Value of High CXCR4 Expression in Renal Cell Carcinoma: A System Review and Meta-Analysis. (7th October 2015) - Du, Yuefeng; Long, Qingzhi; Guan, Bing; Mu, Lijun
Abstract : Background . Recent studies have shown that CXC chemokine receptor 4 (CXCR4) is involved in the progression and metastasis of renal cell carcinoma (RCC). However, the prognostic value of CXCR4 expression in RCC remains controversial. The aim of our meta-analysis is to evaluate the prognostic value of high CXCR4 expression in RCC. Methods . Relevant studies focused on the relationship between high CXCR4 expression and the outcome of RCC were searched in PubMed and EMBASE/Cochrane Library database. Hazard ratios (HRs) of overall survival (OS) and progression-free survival (PFS) were our evaluation index. The individual and pooled HRs with 95% confidence intervals (CIs) were analyzed. Results . A total of 1068 patients from 7 studies were included in our meta-analysis. The results suggested that high CXCR4 expression predicted a poor OS (random effect model (REM) HR = 2.77, 95% CI = 1.80−4.27) and PFS (REM HR = 4.83, 95% CI = 2.30−10.15) for RCC patients. Conclusion . The results of meta-analysis indicated that high CXCR4 expression was correlated with worse OS and PFS for patients with RCC. However, some larger samples and well-matched studies should be designed to estimate the potential prognosis of RCC patients.